Estudo da viabilidade do emprego do pó de mármore para produção de concreto autoadensável e substituição parcial dos agregados por pérolas de poliestireno expandido (EPS) - Kumayama, Rosemarie [UNESP] (2014)
This paper presents a study on the feasibility of using marble powder (civil construction residue) as fine part in the making of self-compacting concrete (SCC) and the replacement of amounts of the large and small parts by expanded polystyrene (EPS) in the proportion of 10%, 20%, 30% and 40%. In the search of correct environmental solutions to minimize the inadequate disposal of this material in the environment re-using them and rheological improvement in the hardened state of SCC. The compositions were optimized and the tests were performed in the fresh state for the validation of the SCC, including the Slump Flow Test, Slump Flow T50 Test, V-Funnel Test, L-Box Test, Sieving Test, Apparent Specific Mass Test. Tests of the hardened state of SCC were also performed for 7 and 28 days, involving the tests of axial and diametral compression, modulus of elasticity, and absorption at 35 days. In the fresh state, there was influence in the sense that the gradual incorporation of EPS to the marble powder contributed to the increase of the property values that depend on the concrete viscosity, to minimize the effects of segregation and exudation; also, contributed to the increase of fluidity. As for the tests in the hardened state, it was noticed that when the expanded polystyrene percentage was increased, the values of the concrete resistance and the modulus of elasticity presented a proportional decrease to the increment values; and, regarding the absorption tests, there was an increase on the values of the absorption with the values of EPS increments